Entrepreneurship in higher education: The key role of self-efficacy-A cross sectional study - Ramalho, José (2022)
Entrepreneurship is the engine of a nation's economic, cultural, and social development. Since Higher Education Institutions play a crucial role, it is important to analyze the academy's entrepreneurial education effectiveness in promoting entrepreneurial intention amongst students. This study aims to analyze the effect of the education agenda of a Higher Education Institution on the students’ entrepreneurial intention, exploring the effect of self-efficacy as a mediator. A quantitative, cross-sectional, and non-experimental study was performed. A sample of 176 Portuguese higher education students fulfilled the “Entrepreneurial Motivations Survey,” which includes the HEInnovate Self-Assessment Scale, the Self-Efficacy Scale, and the Entrepreneurial Intention Scale. Data analysis was performed using Statistical Package for Social Sciences (SPSS), AMOS, and PROCESS software. Through structural equation models, it was created a mediation model to assess the impact of the University education agenda on the entrepreneurial intention of the students. All scales showed adequate validity and reliability. The Faculty was not perceived as an entrepreneurial academy by the students. The results did not show a direct effect of the entrepreneurial education agenda on the students’ entrepreneurial intention. The effects emerged through self-efficacy, which plays a mediating effect between entrepreneurial education agenda on the students’ entrepreneurial intention. The entrepreneurship agenda didn’t directly influence the entrepreneurial intention. It is mandatory to offer a rich agenda in order to improve the students’ entrepreneurial competencies, preparing them to strive in the competitive market, in which self-efficacy plays an important role.